100 (3acQI aj OhGFQ GdCYeGd gj GdGYXe aj cd hbJ (B/s - (3dGfLOhf, cfs; (3GdNRGej, YHO GdMcje CMeO s ((3GdbGgQI(B: s (3GjJQGc ddfTQ h GdJhRjY(B, s, 2007)
(3jVe JSYI GHJcGQGJ HjYjI YXjeI, YTQ GSJQGJjLjGJ YXjeI ddedUbGJ GdeQLYjI, CQHYI JQGNjU YXjeI dWHY GdCehGd, CYXe NeS WQb dJMbjb GdecSH aj HhQUI GdChQGb GdeGdjI, CQHYI QLGd HGFYjf YXGe ef GdHGH Edi GdHGH, ef VQhQjGJ GdeGdjI YXjeI aj MjGI OhGFQ GdCYeGd, CcHQ NeS YdGeGJ JLGQjI aj Cj hbJ, CYXe ef eacQj GdEOGQI, CQHYI GNJQGbGJ YXjeI bGe HgG GdEYdGfs
Keywords: (3EOGQI GdCYeGds